Structure-Activity Relationships (SARs) of α-Ketothioamides as Inhibitors of Phosphoglycerate Dehydrogenase (PHGDH) - Quentin Spillier; Séverine Ravez; Judith Unterlass; Cyril Corbet; Charline Degavre; Olivier Feron; Raphaël Frédérick (MDPI AG, 2020)
For many years now, targeting deregulation within cancer cells’ metabolism has appeared as a promising strategy for the development of more specific and efficient cancer treatments. Recently, numerous reports highlighted the crucial role of the serine synthetic pathway, and particularly of the phosphoglycerate dehydrogenase (PHGDH), the first enzyme of the pathway, to sustain cancer progression. Yet, because of very weak potencies usually in cell-based settings, the inhibitors reported so far failed to lay ground on the potential of this approach. In this paper, we report a structure−activity relationship study of a series of α-ketothioamides that we have recently identified. Interestingly, this study led to a deeper understanding of the structure−activity relationship (SAR) in this series and to the identification of new PHGDH inhibitors. The activity of the more potent compounds was confirmed by cellular thermal shift assays and in cell-based experiments. We hope that this research will eventually provide a new entry point, based on this promising chemical scaffold, for the development of therapeutic agents targeting PHGDH.